2019
DOI: 10.3389/fpls.2019.00263
|View full text |Cite
|
Sign up to set email alerts
|

IRE1-bZIP60 Pathway Is Required for Nicotiana attenuata Resistance to Fungal Pathogen Alternaria alternata

Abstract: As an endoplasmic reticulum (ER) stress sensor, inositol-requiring enzyme 1 (IRE1) splices the bZIP60 mRNA, and produces an active bZIP60 transcription factor that regulates genes involved in the unfolded protein response (UPR) during ER stresses. This IRE1-bZIP60 pathway is conserved in plant species and recently implicated in plant-pathogen interaction. However, it is unclear whether this IRE1-bZIP60 pathway is involved in Nicotiana attenuata resistance to necrotic fungal pathogen, Alternaria alternata. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 42 publications
(59 reference statements)
6
28
0
Order By: Relevance
“…Our results showed that the micromolar concentration of exogenous JA significantly induced the transcript accumulation of BiP within 6 h in the leaves of tomato plants. This could have great importance because earlier, it has been found only that the exogenous application of JA or SA in millimolar concentration increased the expression of BiP genes in Arabidopsis [33] or in soybean [30]. In this work, JA was applied in two different micromolar concentrations, which could be closer to the natural endogenous changes in plants upon pathogen infection [74,75].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Our results showed that the micromolar concentration of exogenous JA significantly induced the transcript accumulation of BiP within 6 h in the leaves of tomato plants. This could have great importance because earlier, it has been found only that the exogenous application of JA or SA in millimolar concentration increased the expression of BiP genes in Arabidopsis [33] or in soybean [30]. In this work, JA was applied in two different micromolar concentrations, which could be closer to the natural endogenous changes in plants upon pathogen infection [74,75].…”
Section: Discussionmentioning
confidence: 95%
“…Firstly, Moreno et al [42] tested the effects of methyl jasmonate (MeJA) in Arabidopsis. Their results showed that 0.03 mM MeJA failed to activate bZIP60 mRNA processing within 5 h. More recently, Xu et al [33] demonstrated that MeJA in the concentration of 1 mM can transiently induce UPR marker genes within 3 h. The expression of BiP, protein disulfide isomerase (PDI), calnexin (CNX), and calreticulin (CRT) was at its maximum after 3 h but the transcript levels of bZIP60 were significantly higher after 12 h in Arabidopsis exposed to 1 mM MeJA [33]. These gene expression data suggest a rapid and concentration-dependent effect of MeJA, but the biochemical and physiological changes have neither been investigated in Arabidopsis nor in crops.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Biotin-labeled synthetic oligonucleotide was annealed with unlabeled oligonucleotides and then used as probes. A DNA protein-binding reaction was performed using a LightShift R Chemiluminescent EMSA Kit (Pierce) according to the previous description (Xu Z. et al, 2019). Briefly, the labeled DNA fragments were incubated for 25 min with 180 ng of the recombinant protein in binding buffer [10 mM Tris (pH 7.5), 1 mM DTT, 2.5% glycerol, 50 mM KCL, 10 mM MgCl 2 , 0.1% Nonidet P-40, and 50 ng/µL poly (dI-dC)].…”
Section: Emsa Analysismentioning
confidence: 99%
“…Solanum species treated leaves with DTT or NaCl and carried out time course experiments to demonstrate that the transcriptional response of several UPR related genes including BiP can be seen as early as between 1 and 4 h after treatment using RT-qPCR [25][26][27][28][29][30] . For simplicity in this study, we infiltrated potato leaves with 2 mM DTT or 150 mM NaCl to induce ER stress and measured BiP transcript levels after 4 h of treatment 30,31 .…”
Section: Potato Bips Are Differentially Expressed Under Developmentalmentioning
confidence: 99%